The Interests of Family Medicine Residents in Future Faculty Positions Across the Senior Year. (November 2021) - Weidner, Amanda; McGuire, Marcia; Stutzman, Kim; Glass, Justin; Stevens, Nancy Gray
Background and Objectives: The shortage of residency faculty in the pipeline is a growing concern to meet future workforce needs, though there is little research on attracting residents to be future faculty or what factors would influence their interest in this role. The objectives of this study were: (1) To assess the interest of third year residents (R3s) in faculty positions, and the various factors that might positively or negatively affect this decision; (2) to compare whether this changes across the R3 year; and (3) to compare between chief residents and other R3s. Methods: Longitudinal survey at two points in time for each of three consecutive cohorts of R3s (2016-2018) from a regional network of family medicine residency programs. Results: Among the final sample of R3s (176/545, 32% response), nearly half were interested in a residency faculty role. Strong positive influences on interest include the teaching role, advising/mentoring role, range of practice scope, and ability to perform procedures; salary and administrative responsibilities detract from interest. Among the matched sample of 96 R3s who also responded at Time 2 (55% response), non-chief residents had an increase in knowledge of and interest in the faculty role across the R3 year. Conclusions: Nearly half of senior family medicine residents report positive interest in residency faculty positions and in most components of the role. Mentorship may encourage more residents to consider these positions upon graduation or shortly thereafter. More research on other specialties and with career follow up is recommended.